Hydrologic extremes in a changing climate: a review of extremes in East Africa - Taye, Meron Teferi; Dyer, E. (Springer, 2024)
Purpose: Eastern Africa has a complex hydroclimate and socio-economic context, making it vulnerable to climate change induced hydrological extremes. This review presents recent research on drivers and typologies of extremes across different geographies and highlights challenges and improvements in forecasting hydrological extremes at various timescales. Recent Findings: Droughts and foods remain the major challenges of the region. Recently, frequent alterations between droughts and foods have been a common occurrence and concern. Research underlines the heterogeneity of extremes and the impact of climate change as increased intensity and duration of extremes. Moreover, the importance of local and antecedent conditions in changing the characteristics of extremes is emphasized. Summary: A better understanding of these drivers and how they interact is required. Observational and modeling tools must capture these relationships and extremes on short timescales. Although there are improvements in forecasting these extremes, providing relevant information beyond meteorological variables requires further research.